Суспільні настрої в Україні у ході чехословацької кризи 1968 року за донесеннями радянських спецслужб - Бажан, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2008)
Based on the unknown documents from the State archive of Security Service of Ukraine, the author investigated reaction of the Ukrainians on the events of «Prague spring» of 1968, as well as actions of communist authority of the USSR aimed at suppression of attempts to democratize of Czechoslovakia.